The human T-cell receptor. - Acuto, O; Fabbi, M; Bensussan, A; Milanese, C; Campen, T; Royer, H; Reinherz, E (1985)
Recent studies using cloned antigen-specific T lymphocytes and monoclonal antibodies directed at their various surface glycoprotein components have led to the identification of the human T-cell antigen receptor as a surface complex comprised of a clonotypic 90-kD Ti heterodimer and the invariant 20- and 25-kD T3 molecules. Approximately 30,000-40,000 Ti and T3 molecules exist on the surface of human T lymphocytes. These glycoproteins are acquired and expressed during late thymic ontogeny, thus providing the structural basis for immunologic competence. The alpha and beta subunits of Ti bear no precursor-product relationship to one another and are encoded by separate genes. Moreover, the presence of unique peptides following proteolysis of different Ti molecules isolated by non-cross-reactive anticlonotypic monoclonal antibodies supports the notion that variable regions exist within both the alpha and the beta subunits. N-Terminal amino acid sequencing and molecular cloning of the Ti beta subunit further show that it bears an homology to the first V-region framework of immunoglobulin light chains and represents the product of a gene that rearranges specifically in T lymphocytes. Triggering of the T3-Ti receptor complex gives rise to specific antigen-induced proliferation through an autocrine pathway involving endogenous IL-2 production, release, and subsequent binding to IL-2 receptors. The implications of these findings for understanding human T-cell growth and its regulation in disease states are discussed.